THE USE OF STAPHYLOCOCCAL LIQUID BACTERIOPHAGE IN THE TREATMENT OF CHILDREN WITH OBSTRUCTIVE BRONCHITIS AND AN ASSESSMENT OF ITS EFFECTIVENESS - Ilmuratova Munisa Abduqayum qizi (Scientific Impulse, 2023)
children,obstructive bronchitis,staphylococcal liquid bacteriophage Relevance of the problem: obstructive bronchitis disease is an inflammatory disease of the bronchi, accompanied by obstruction of the bronchi. It is considered one of the most common diseases of the respiratory system in young children and is more common in children between 6 months and 5 years of age. The disease is mainly caused by children with weak immunity, who often get sick. The constant use of antibiotics leads to a further decrease in the protective functions of the child's body. Global Studies in recent years show that the use of bacteriophages in respiratory system organs, in particular in bronchopulonary pathologies, is highly effective.